1999
DOI: 10.1002/(sici)1098-2795(199907)53:3<294::aid-mrd5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA encoding insulin-like growth factors I and II by uterine tissues and placenta during pregnancy in the rat

Abstract: The uterus and the placenta synthesize insulin‐like growth factors (IGFs) and insulin‐like binding proteins (IGFBPs). These growth factors are implicated in processes of proliferation and differentiation that occur in the uterus. To determine the patterns of expression of IGFs during rat pregnancy we used in situ hybridization with digoxigenin labeled probes on uterus from day 7 to day 16 of pregnancy. In early gestation days (7–8) both IGF mRNAs showed similar tissue distribution with relative abundance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The uterus also expressed high levels of mRNA for IGF-I. Previous studies in pregnant rats (Correia-Da-Silva et al 1999) and pigs (Sterle et al 1998) also showed an expression of mRNA for IGF-I in uterus, although it was not compared with other tissues besides the placenta. Consistent with our results, low levels or no expression of mRNA for IGF-I have been detected in the placenta in guinea pigs (Han et al 1999) and rats (Möller et al 1991).…”
Section: Discussionmentioning
confidence: 85%
“…The uterus also expressed high levels of mRNA for IGF-I. Previous studies in pregnant rats (Correia-Da-Silva et al 1999) and pigs (Sterle et al 1998) also showed an expression of mRNA for IGF-I in uterus, although it was not compared with other tissues besides the placenta. Consistent with our results, low levels or no expression of mRNA for IGF-I have been detected in the placenta in guinea pigs (Han et al 1999) and rats (Möller et al 1991).…”
Section: Discussionmentioning
confidence: 85%
“…An important growth factor in placental development is IGF2 (Redline et al, 1993;Correia-da-Silva et al, 1999). Also, Igf 2 is an imprinted gene, and it has been shown recently that imprinting may be disrupted in interspecific Peromyscus hybrids (Vrana et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of the placenta is regulated by several growth factors, including placental growth factor (PlGF), vascular endothelial growth factor (VEGF), and fibroblast growth factor-2 [1, 14, 15]. These growth factors are responsible for fetal development as well as placenta growth [5,9,20,22]. PlGF is a polypeptide growth factor that shares a 53% amino acid sequence homology with the platelet-derived growth factor domain of VEGF [17].…”
mentioning
confidence: 99%